2010
DOI: 10.1103/physrevb.81.134440
|View full text |Cite
|
Sign up to set email alerts
|

Spin-glass-like properties ofLa0.8Ca0.2MnO3nanoparticles ensembles

Abstract: Magnetic properties of compacted La 0.8 Ca 0.2 MnO 3 manganite nanoparticles with average particle size of 18 and 70 nm and Curie temperatures T C Ϸ 231 K and T C Ϸ 261 K, respectively, have been investigated. The relative volume of the ferromagnetic phase has been estimated to be 52% for ensembles of 18 nm particles and 92% for 70 nm particles. It was found that applied hydrostatic pressure enhances T C of La 0.8 Ca 0.2 MnO 3 nanoparticles at a rate dT C / dP Ϸ 1.8-1.9 K / kbar, independently on the average p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 72 publications
4
58
0
Order By: Relevance
“…35 MnO 3 thin films grown on SrTiO 3 by gating with ionic liquid in electric double layer transistors (EDLT). In such manganite films with strong phase separation, a cluster glass magnetic state emerges at low temperatures with a spin freezing temperature of about 99 K, which is accompanied by the reentrant insulating state with high resistance below 30 K. In the EDLT, we observe bipolar and asymmetric modulation of the channel resistance, as well as an enhanced electroresistance up to 200% at positive gate bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 MnO 3 thin films grown on SrTiO 3 by gating with ionic liquid in electric double layer transistors (EDLT). In such manganite films with strong phase separation, a cluster glass magnetic state emerges at low temperatures with a spin freezing temperature of about 99 K, which is accompanied by the reentrant insulating state with high resistance below 30 K. In the EDLT, we observe bipolar and asymmetric modulation of the channel resistance, as well as an enhanced electroresistance up to 200% at positive gate bias.…”
mentioning
confidence: 99%
“…Prototypical PS manganites like La 5/8Ày Pr y Ca 3/8 MnO 3 (LPCMO) and Pr 0.65 (Ca y Sr 1Ày ) 0. 35 MnO 3 (PCSMO) have been extensively investigated. [5][6][7][8][9][10][11] In general, the dynamic fluid-like PS states and their glassy nature sensitively depend on the external parameters like temperature, magnetic field, and electric field.…”
mentioning
confidence: 99%
“…The features mentioned above indicate that Ca 2 CrO 4 exhibits spin glass magnetic behavior. 22,23 Temperature dependence of electrical resistivity of the sample exhibits an insulating behavior as shown in Fig. 6, the data below 70 K was absent for out of measurement limit.…”
Section: Resultsmentioning
confidence: 99%
“…9) and La 0.8 Ca 0.2 MnO 3 (Ref. 25). We also suggested that the difference between the Mn neighborhood inside the crystalline core and disordered local structure of the outer shell matrix causes the broadening of the XANES spectrum of the NP2 powder.…”
Section: Resultsmentioning
confidence: 99%